2020
DOI: 10.33963/kp.15603
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc score as a predictor of no-reflow phenomenon after saphenous vein graft percutaneous coronary intervention in patients with non–ST-segment elevation acute coronary syndromes

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This is in harmony with Mirbolouk et al (10) who reported that, the mean CHA2DS2-VASc score was 1.6 ± 1.4 and it was significantly higher in the no-reflow group compared to the control group (3 ± 1.4 versus 1.1 ± 1.1, P < 0.001). This also agreed with Gürbak et al (17) who aimed to investigate the relationship between the CHA2DS2-VASc score and no-reflow phenomenon after SVG PCI in patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS). They reported that the CHA2DS2-VASc score (P <0.001) was significantly higher in no-reflow group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in harmony with Mirbolouk et al (10) who reported that, the mean CHA2DS2-VASc score was 1.6 ± 1.4 and it was significantly higher in the no-reflow group compared to the control group (3 ± 1.4 versus 1.1 ± 1.1, P < 0.001). This also agreed with Gürbak et al (17) who aimed to investigate the relationship between the CHA2DS2-VASc score and no-reflow phenomenon after SVG PCI in patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS). They reported that the CHA2DS2-VASc score (P <0.001) was significantly higher in no-reflow group.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, Zhang et al ( 14) demonstrated that the CHADS2, CHA2DS2-VASc, score was independent predictor of NRP after PPCI in patients with STEMI. In addition, Gürbak et al (17) reported that, receiver operating characteristics analysis showed that a CHA2DS2-VASc score of 4 predicted no-reflow phenomenon with 67.9% sensitivity and 69.3% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…3 CHA 2 DS 2 and CHA 2 DS 2 -VASc score models are widely used to predict the risk of subsequent thromboembolic events in patients with atrial fibrillation (AF) and include similar risk factors for the development of CAD. 4,5 Recent evidence has shown that the CHADS 2 score has prognostic ability in CAD, 6,7 regardless of the presence of AF, 8 and has suggested the power of CHADS 2 and CHA 2 DS 2 -VA to assess major adverse cardiovascular outcomes in the setting of ACS. 9 Moreover, a retrospective study found that the CHA 2 DS 2 -VASc score was associated with a higher risk of in-hospital mortality rates in patients who underwent primary percutaneous coronary intervention (PCI) for STEMI.…”
mentioning
confidence: 99%
“…Both ACS and SVG interventions are risk factors for the development of no-reflow [ 24 ]. In Gürbak et al ’s study, the rate of no-reflow development was 29% in interventions performed in the SVG [ 25 ]. In another study, this rate was 18% in patients undergoing PCI of the SVG [ 26 ].…”
Section: Discussionmentioning
confidence: 99%